Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 25831 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Buteo swainsoni Bonaparte, 1838", "Geometry POLYGON((-118.388671 33.137551,-118.388671 15.029685,-86.220703 15.029685,-86.220703 33.137551,-118.388671 33.137551))" ] } The dataset includes 25831 records from 45 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003575-150615163101818/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences